Experimental Investigation of Hydrocarbon-fuel Ignition in Scramjet Combustor - 宋文艳 黎明 蔡元虎 刘伟雄 白菡尘 (Chinese journal of aeronautics, 2004)
The direct-connected supersonic combust or experiment is finished for kerosene fuel ignition in H2/O2 preheated impulse facility. The entrance parameter of combustor corresponds to scram jet flight Mach number 3.5. Kerosene ignition is realized by using hydrogen as pilot flame. Wall pressure distributions of combustion are measured and flame photographs of ultraviolet ray are got. Experiment indicates that it is very difficult for kerosene fuel to realize self-ignition at low entrance temperature (below 900K) in supersonic combustor. Hydrogen pilot flame is one of the efficient methods for realizing kerosene ignition.